1997
DOI: 10.1098/rspb.1997.0070
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric specialization for global and local processing: the effect of stimulus category

Abstract: SUMMARYNeuropsychological evidence indicates that the global aspect of complex visual scenes is preferentially processed by the right hemisphere, and local aspects are preferentially processed by the left hemisphere. Using letter-based hierarchical stimuli (Navon figures), we recently demonstrated, in a directed-attention task, lateralized neural activity (assessed by positron emission tomography) in the left prestriate cortex during local processing, and in the right prestriate cortex during global processing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
74
3
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(87 citation statements)
references
References 25 publications
8
74
3
1
Order By: Relevance
“…For instance, of three studies in which positron emission tomography was used to asses brain activity during local and global processing, only one showed effects in the expected direction (Fink et al, 1996). The other two either failed to replicate this result (Heinze, Hinrichs, Scholz, Burchert, & Mangun, 1998) or even showed a reversed effect (Fink, Marshall, Halligan, Frith, & Frackowiak, 1997). Mixed results are also present in studies measuring event-related brain potentials (ERPs; e.g., Han, Fan, Chen, & Zhuo, 1999;Heinze & Münte, 1993;Johannes, Wieringa, Matzke, & Münte, 1996) as well as in neuropsychological studies.…”
mentioning
confidence: 76%
“…For instance, of three studies in which positron emission tomography was used to asses brain activity during local and global processing, only one showed effects in the expected direction (Fink et al, 1996). The other two either failed to replicate this result (Heinze, Hinrichs, Scholz, Burchert, & Mangun, 1998) or even showed a reversed effect (Fink, Marshall, Halligan, Frith, & Frackowiak, 1997). Mixed results are also present in studies measuring event-related brain potentials (ERPs; e.g., Han, Fan, Chen, & Zhuo, 1999;Heinze & Münte, 1993;Johannes, Wieringa, Matzke, & Münte, 1996) as well as in neuropsychological studies.…”
mentioning
confidence: 76%
“…A functional MRI (fMRI) study found similar hemispheric asymmetry in whole-part processing over the occipitotemporal cortical junctions (8). However, other studies failed to replicate such RH-whole/LH-part asymmetry (9).…”
mentioning
confidence: 83%
“…The presence of the two pathways has also been suggested in humans in neuropsychological studies of patients 4)5) and by positron emission tomography (PET) in normal subjects [6][7][8] . Furthermore, it is known that brain function is related to attention, cognition and memory of visual spaces and objects are asymmetrically located in the left and right hemispheres [9][10][11] .…”
mentioning
confidence: 99%